Pengaruh Sudut Pengarah Aliran dan Jumlah Sudu Radius Berengsel Luar Roda Tunggal terhadap Kinerja Turbin Kinetik - Maidangkay, Adrian; Soenoko, Rudy; Wahyudi, Slamet (Jurnal Rekayasa Mesin, 2014)
The aimof this research was to know kinetic turbine performance feat influence onguide angle of the water input flow and the amount of outter radius blade hinged of single wheel. Kinetic turbine was used in this research, it has vertical axes with three guide angle variations of 150, 250, and 350 and also the amount of blades is 8, 10 and 12. The results showed that the guide angle of flow and the amount of blades influence the kinetic turbine performance (power, efficiency, and torque). The guide angle of flow and the amountof blade out hinged radius of single wheel influences the kinetic turbine performance. From several angle variation of guide angle and the amount of blade out hinged radius of single wheel under observation, the turbine performance with guide angle of flow 350 higher than 250 and 150. The performance of 12 blades turbine is higher than turbine with blades of 10 and 8. The higher guides angle the more blades, the higher tangential force, torque, power and efficiency. The maximum performance of kinetic turbine occurs at the guide angle of flow 350, the blades amount 12, revolution 90 rpm, water capacity 50m3/hour and with produced power, efficiency and torque are 21.365 Watt, 33,241 %, and 3.864 N.m respectively.Keywords: Kinetic Turbine, Performance, Guide Angle of Flow, Amount of Blade